Talleres de trabajo comunitario: una experiencia de innovación pedagógica - Sancho, Jordi; Llobet Estany, Marta; Tous, Josep María; Barbero, Manuel; Cortés, Ferrán (Acciones e Investigaciones Sociales, 2011)
Talleres de trabajo comunitario: una experiencia de innovación pedagógica